Elemental and Proximate Compositions of Sesame Seeds and the Underlying Soil from Tsegede, Ethiopia - Fuad Seid; Bewketu Mehari (International Journal of Analytical Chemistry)
The proximate compositions and elemental contents of sesame (Sesamum indicum) seeds and the underlying soil from different cultivation areas of Tsegede, Ethiopia, were investigated. The ash, protein, fiber, fat, and carbohydrate contents of the sesame seeds were determined following standard methods. Essential major (Ca and Mg) and trace metals (Fe, Zn, Cu, Mn, and Ni) in the sesame seeds and the underlying soil were determined by using flame atomic absorption spectroscopy. The sesame seeds contained high levels of fat (52.9 ± 1.5%), followed by protein (23.5 ± 0.9%). The seeds contained 525 ± 1 and 453 ± 38 mg/kg of Mg and Ca, respectively. Iron was the most abundant (37.8 ± 1.4 mg/kg) of the trace metals, followed by Zn (14.6 ± 2.2 mg/kg) and Cu (7.26 ± 0.84). Manganese and Ni were found only in minute amounts. The concentrations of the trace metals varied significantly across the different cultivation areas. Similar to the sesame seeds, iron was found in higher amounts (212.6 ± 2.6 mg/kg) in the underlying soil followed by Zn and Cu, which were both 28.8 mg/kg. The amounts of the trace elements, Fe, Cu, and Zn found in the soils were about 2 to 6 times higher than that found in the sesame seeds. Whereas, the concentrations of Mg and Ca present in the seeds were comparable with that determined in the soils. Correlation analysis indicated that the Fe and Cu contents of the sesame seeds are negatively influenced by the amounts of Mg and Ca present in the soil. Ca in the seeds was also negatively associated with the Mg levels in soil.